In-Game Spending Due To Quarantine: A Case Study Of Batam Region - Nelson Donglas; Tony Wibowo (Universitas Internasional Batam, 2023)
Pandemic mitigation measures greatly affect our social development now, measures such as wearing masks, maintaining distance, and quarantine have been used to prevent the spread of the virus. As a result of the precautions taken, outdoor stress-relieving activities may become prohibited or impractical due to social distancing measures. People who must stay at home and need a social life must look for other activities to avoid anxiety and stress. Video games have become an excellent alternative to avoid this problem, the ability of people to cope with stress thanks to video games and social interactions through online games has increased the consumption of digital games. The main aims of this study are firstly to analyse changes in players money spending due to quarantine and secondly to investigate any changes in gaming behaviour due to quarantine. To do so, 380 participants were invited to complete an online survey to answer questions regarding video games and quarantine. The results showed that there was an increase in player playtime during the quarantine period, more people brought in their families and friends to play together and there was an increase on players spending money on video games. Correlation between post-pandemic and in-game purchase behaviour should be evaluated in further studies.